Teachers’ Perception on Effects of ICT Tools in Teaching Science at Secondary Level (Research Journal on Multi-disciplinary Issues, 2021)
In this digital era, the use of ICT tools in teaching learning has been increasing day by day. This study, therefore, focuses on teachers’ perception on effects of ICT tools in science teaching classes. The objectives of the study were to identify the existing situation of the use of ICT tools in science teaching and to find perceptions of teachers towards effects of ICT tools in effective classroom teaching in both public and private schools. 12 science teachers one from each school and 12 secondary schools: six public and six private of Siraha district were selected randomly as population of the study. This study followed quantitative survey research design. The data were collected through questionnaire, observation and group discussion. The data showed that the teachers used various  ICT tools but they have to face various challenges due to poor infrastructure, limited accessibility, poor network connection, insufficient technical support and lack of effective training. It was found that private school teachers had higher perspectives than public school teachers due to age factor and competency of ICT knowledge and practice. This project is hopeful to provide proper information and suggestions to those who are responsible for integrating new technologies in science teaching.